Risk stratification of sudden cardiac death in heart failure patients: is left ventricular ejection fraction alone sufficient? - N. N. Ilov; Olesya V. Palnikova; D. R. Stompel; E. V. Nikolaeva; A. A. Nechepurenko (Российский кардиологический журнал)
According to current clinical guidelines, the risk of sudden cardiac death (SCD) in patients with heart failure is specified by left ventricular (LV) ejection fraction (EF). We believe that risk stratification and choice of patient management tactics should be based on modern diagnostic techniques aimed at identifying the anatomical and electrophysiological substrate of SCD. Therefore, LVEF alone is not enough to solve such problems. This review presents an analysis of current research on the novel predictors of SCD. The most promising areas include the identification of electrocardiological markers of fatal ventricular arrhythmias, modern ultrasound and magnetic resonance imaging techniques. The importance of electrophysiological tests in the verification of SCD risk is discussed. Based on the literature analysis, we can conclude that only a combination of different factors can significantly increase the diagnostic value of prognostic model and improve the primary prevention of SCD.